Assessment of stress levels among teachers of learners with special needs in primary schools in Mbarara District, Uganda - Atukunda, Judith; Kemeza, Imelda (International Journal of Advance Research, Ideas and Innovations in Technology, 2020)
Teachers of learners with special needs in primary schools are faced with different stress levels associated with special needs learners, for example, limited support, poor students’ behavior, un friendly classroom environment and poor professional competency. This paper explored the levels of stress among teachers handling learners with special needs in primary schools of Mbarara Municipality-Uganda. Census was used on the entire population of 53 teachers, purposive sampling was used to select schools handling learners with special needs. Data was collected using a cross-sectional survey design with quantitative and qualitative methods, a structured and open-ended questionnaire. The questionnaire composed of demographic section including total number of years in teaching, positions held in school, highest academic qualification, and formal education under taken for teaching special needs cases. Results show that majority of the respondents were males 27(50.9%), teachers who had an experience of teaching for ten years and above (56.6%), class teachers (52.8%), teachers with diplomas (54.7%), and teachers who had informal education on handling learners with special needs (56.6%). It was further discovered that teachers experienced high levels of stress due to limited support (M = 32.92, SD =9.52), and due to behavior of the students (M = 61.25, SD =15.92). The study recommends that teachers handling learners with special needs be supported by school administrators through refreshers courses to adequately handle learners in a friendly environment.
Keywords: Stress Levels; Teachers; Special needs